Brain plasticity and sensorimotor deterioration as a function of 70 days head down tilt bed rest - Koppelmans, Vincent; Bloomberg, Jacob J.; De Dios, Yiri E.; Wood, Scott J.; Reuter-Lorenz, Patricia A.; Kofman, Igor S.; Riascos, Roy; Mulavara, Ajitkumar P.; Seidler, Rachael D. (PloS one, 2017)
Adverse effects of spaceflight on sensorimotor function have been linked to altered somatosensory and vestibular inputs in the microgravity environment. Whether these spaceflight sequelae have a central nervous system component is unknown. However, experimental studies have shown spaceflight-induced brain structural changes in rodents' sensorimotor brain regions. Understanding the neural correlates of spaceflight-related motor performance changes is important to ultimately develop tailored countermeasures that ensure mission success and astronauts' health. Head down-tilt bed rest (HDBR) can serve as a microgravity analog because it mimics body unloading and headward fluid shifts of microgravity. We conducted a 70-day 6° HDBR study with 18 right-handed males to investigate how microgravity affects focal gray matter (GM) brain volume. MRI data were collected at 7 time points before, during and post-HDBR. Standing balance and functional mobility were measured pre and post-HDBR. The same metrics were obtained at 4 time points over ~90 days from 12 control subjects, serving as reference data. HDBR resulted in widespread increases GM in posterior parietal regions and decreases in frontal areas; recovery was not yet complete by 12 days post-HDBR. Additionally, HDBR led to balance and locomotor performance declines. Increases in a cluster comprising the precuneus, precentral and postcentral gyrus GM correlated with less deterioration or even improvement in standing balance. This association did not survive Bonferroni correction and should therefore be interpreted with caution. No brain or behavior changes were observed in control subjects. Our results parallel the sensorimotor deficits that astronauts experience post-flight. The widespread GM changes could reflect fluid redistribution. Additionally, the association between focal GM increase and balance changes suggests that HDBR also may result in neuroplastic adaptation. Future studies are warranted to determine causality and underlying mechanisms.